2017
DOI: 10.1080/13803395.2017.1321106
|View full text |Cite
|
Sign up to set email alerts
|

Working memory predicts presence of auditory verbal hallucinations in schizophrenia and bipolar disorder with psychosis

Abstract: The findings of this study-the first, to our knowledge, to compare the relationship between AVHs and MATRICS domains across schizophrenia and bipolar disorder with psychosis-support theories that deficits in WM underly the genesis of AVHs. WM potentially represents a shared mechanism of AVHs across diagnoses, supporting dimensional classifications of these psychotic disorders. However, non-cognitive factors predictive of hallucination severity may be specific to schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 48 publications
5
38
0
2
Order By: Relevance
“…It has also been known that the left SFG plays a critical role in mediating working memory [ 75 ]. The recent Jenkins et al study (2017) [ 76 ] has provided evidence showing that working memory can be used for predicting the presence of AVH in both people with schizophrenia and those with bipolar disorder. Thus, deficits in working memory may share some underlying mechanisms with the genesis of AVH and the involvement of the left SFG in hallucinations may be caused by the functional impairment of this cortical region in working memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been known that the left SFG plays a critical role in mediating working memory [ 75 ]. The recent Jenkins et al study (2017) [ 76 ] has provided evidence showing that working memory can be used for predicting the presence of AVH in both people with schizophrenia and those with bipolar disorder. Thus, deficits in working memory may share some underlying mechanisms with the genesis of AVH and the involvement of the left SFG in hallucinations may be caused by the functional impairment of this cortical region in working memory.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that working memory is underlying the involvement of the left SFG in both visual search [ 87 , 88 ] and the EEM that can be efficiently measured with RSS [ 12 ]. Since deficits in working memory share some underlying mechanisms with the genesis of AVH [ 76 ], the negative correlation between the hallucination severity and the GMV in the left SFG and positive correlation between the RSS score and the GMV of the left SFG suggest that schizophrenia-related hallucinations and RSS deficits may be associated with deficits in working memory.…”
Section: Discussionmentioning
confidence: 99%
“…Working memory impairments in CBP+ may also be localized to more demanding working memory measures (Frydecka et al 2014). One study demonstrated that working memory impairments are specifically related to the presence of hallucinations (Jenkins et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Patients met the following criteria: (1) <3 years of illness onset; (2) mental capacity to consent; and (3) diagnosis of schizophrenia/schizoaffective disorder [27]. Healthy volunteers met the following criteria: (1) no current/lifetime history of an Axis I disorder, as determined by the Structured Clinical Interview of DSM-IV-TR Axis I Disorders (SCID) [27]; (2) and no family history (first/second-degree) of an Axis I disorder [28].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Verbal working memory (WM) deficits are a stable component of the cognitive deficit seen in schizophrenia [1] that predict poor clinical [2] and functional outcomes [3]. However, the neurobiology underlying WM impairments remains poorly understood and unaddressed by current treatments [4].…”
Section: Introductionmentioning
confidence: 99%